Ocular melanoma and the BAP1 hereditary cancer syndrome: implications for the dermatologist. (2nd April 2014) - Martorano, Lisa M.; Winkelmann, Richard R.; Cebulla, Colleen M.; Abdel‐Rahman, Mohamed H.; Campbell, Shannon M.
Abstract Ocular melanoma is a rare subtype of melanoma, which includes uveal melanoma (UM) and conjunctival melanoma. UM is associated with an increased risk of cutaneous melanoma (CM) in addition to mesothelioma, skin lesions such as epithelioid atypical Spitz tumors, and other internal malignancies due to a germline mutation of the BRCA1‐associated protein 1 (BAP1) gene. Such familial risks are important for dermatologists to recognize when screening patients with a history of UM for CM and other malignancies. Molecular genetics further help to elucidate the connections between UM and CM by revealing similarities and differences in important mutations among the melanoma subtypes. Both UM and CM have been shown to harbor germline mutation of BAP1. However, somatic mutations in either GNAQ or GNA11 are unique to UM tumors and could be used as potential markers to differentiate UM from metastatic CM and act as direct therapeutic targets. However, CM‐associated BRAF and CDKN2A mutations are rare in UM. This review addresses the clinical features, pathogenesis, and current treatment options of UM, focusing on UM and the BAP1 cancer syndrome to raise awareness of ocular melanoma and its greater role in the predisposition to a hereditary cancer syndrome.